2023
DOI: 10.1017/s0954579422001353
|View full text |Cite
|
Sign up to set email alerts
|

Associations between maternal postpartum depression and infant temperament in treatment-seeking mothers prior to and during the COVID-19 pandemic

Abstract: It remains unclear how the COVID-19 pandemic has affected the mother–infant relationship and associations between maternal postpartum depression (PPD) and offspring temperament. This study examined the impact of the pandemic on these links and how maternal ratings of the mother–infant relationship mediated associations between PPD and infant temperament in a sample of treatment-seeking mothers in Ontario, Canada before and during the COVID-19 pandemic. Mothers with infants <12 months of age and Edinburgh Po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 65 publications
2
3
0
Order By: Relevance
“…Overall, these findings are consistent with previous work finding associations between maternal distress and infant socioemotional development during the COVID‐19 pandemic (Bianco et al., 2022; Chang et al., 2023; Duguay et al., 2022; Provenzi, Grumi et al., 2021). However, there is some inconsistency in the literature with respect to the association between maternal distress during the pandemic and specific domains of infant temperament (i.e., negative affectivity, surgency, effortful control).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Overall, these findings are consistent with previous work finding associations between maternal distress and infant socioemotional development during the COVID‐19 pandemic (Bianco et al., 2022; Chang et al., 2023; Duguay et al., 2022; Provenzi, Grumi et al., 2021). However, there is some inconsistency in the literature with respect to the association between maternal distress during the pandemic and specific domains of infant temperament (i.e., negative affectivity, surgency, effortful control).…”
Section: Discussionsupporting
confidence: 92%
“…However, there is some inconsistency in the literature with respect to the association between maternal distress during the pandemic and specific domains of infant temperament (i.e., negative affectivity, surgency, effortful control). These findings are consistent with research showing that postpartum depression symptoms in women seeking mental health support during the pandemic were associated with more infant negative affectivity ( Chang et al, 2023 ) and that maternal COVID-19 impact score was related to infant negative emotionality ( Bianco et al, 2022 ). However, other studies have found relationships between maternal distress and infant surgency, but not infant negative affectivity ( Provenzi, Mambretti, et al, 2021 ).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…However, given that in many respects this investigation is first of a kind, we prioritized controlling Type 2 error to maintain adequate power. This approach is typical for investigations addressing temperament with similarly sized samples (Balle et al., 2022; Blandon et al., 2010; Zhang et al., 2018) and the influence of pandemic stress on maternal‐child health (Chang et al., 2023; Morales et al., 2021; Morris & Saxbe, 2023; Sacchi et al., 2023). Nonetheless, future studies are needed to follow‐up and discern the most robust pathways of the COVID‐19 pandemic on prenatal mental health and infant temperament.…”
Section: Discussionmentioning
confidence: 99%
“…Buthmann et al (2022) found that pandemicrelated stress was associated with both increased prenatal depressive symptoms and infant negative affect. Comparing women who became mothers before versus during the pandemic, Chang et al (2023) found that the association between postpartum depression and maternal anxiety about the child was stronger during than before the pandemic; further, parental bonding mediated the relation between postpartum depression and infant negative affect across both samples. The COVID-19 pandemic may have also exacerbated associations between parent depression and child mental health.…”
Section: Covid-19mentioning
confidence: 94%